Phytoplankton composition in a eutrophic estuary: Comparison of multiple taxonomic approaches and influence of environmental factors - Weida Gong; Nathan Hall; Hans Paerl; Adrian Marchetti (Environmental Microbiology, 2020)
Summary To assess the comparability between taxonomic identification methods for phytoplankton, multiple approaches were used to characterize phytoplankton community composition within the Neuse River Estuary (NRE), North Carolina. Small subunit 18S rRNA gene sequencing and accessory pigment analysis displayed similar trends, indicating chlorophytes were the dominant microalgal group during most of the year, whereas results from microscopic cell counts, biovolume analysis and metatranscriptomics suggested diatom and dinoflagellate‐dominated communities. Spatial environmental gradients drove variation in taxonomic composition due to preferences for specific environmental conditions among different microalgal groups. Cryptophytes were a greater proportion of the phytoplankton community within high nutrient, fresher environments whereas diatoms and dinoflagellates dominated higher salinity sections of the estuary. This study provides a detailed examination of phytoplankton communities associated with environmental gradients present in the NRE. The high level of taxonomic resolution offered by DNA sequencing (i.e., species to sub‐species level) provides a better understanding of population dynamics at the base of estuarine food webs.